Automated Control Systems for Mutual Loads of Traction Electric Machines - Afanasov, A. M; Arpul, S. V; Vasyliev, V. Y; Hololobova, O. O; Holik, S. M (Science and Transport Progress, 2022)
Purpose. Testing of electric machines should be as objective as possible and contain reliable information about the quality of manufacture or repair of electric machines. During the tests, the parameters of the total power of the test bench sources, energy efficiency of each test process, the difference in thermal loads of the armature windings and excitation windings change. To perform the full test of the electric machine, it is necessary to equip test benches with systems for automatic control of the process of mutual loading. The analysis of different variants of automatic control systems is performed in the work. Methodology. Theoretical studies of electromagnetic processes using a mathematical model of the system “voltage source – traction motor” were performed. This system allows determining the energy performance of electric machines in the entire range of changes in loads and voltages during the tests. The methods of theoretical research and analytical calculation of electrical circuits, theoretical foundations of electrical engineering, mathematical modelling of electrical and energy processes were used in the analysis. Findings. The analysis of rational variants of functional schemes’ construction of automatic control systems with various quantity of power supplies, automatic control loops, mechanical and electric power converters is performed. Rational functional schemes of automatic control systems for testing various collector electric machines of direct and pulsating current are developed. Originality. Rational variants of construction of test benches with electric and mechanical moment converters taking into account variable processes of loading of electric cars during the test are offered. The analysis of energy efficiency of various variants of construction of test benches for testing electric machines in entire range of change of test loadings and voltage of power supplies in the case of using the automatic control system of mutual loading process is performed. Practical value. The conducted research will allow creating recommendations for the design of automated control systems for test benches in order to improve the technical and economic characteristics, reduce the consumption of electricity consumed for testing.